PERANCANGAN APLIKASI PENGELOLAAN ALAT-ALAT RUMAH TANGGA BERBASIS ANDROID PADA UD IMAM JAYA KUTACANE, ACEH TENGGARA - Muhamad Alda; Fatimah; Nuriah Aini; Ainun Fadilah Nst (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
In the household, of course, household appliances are needed to help and simplify all matters in the household. At UD Imam Jaya there are various types of household appliances such as electronic and non-electronic goods, from the many brands and models of household appliances, the goods manager will experience difficulties in managing the data on the goods at UD Imam Jaya. needed to find out the amount of goods or what items are in the warehouse. So in facilitating the management of goods in the warehouse, an application design is needed. So the results of this design are expected to make it easier in terms of searching for the availability of goods, making reports of incoming and outgoing goods transactions and introducing what products are available at UD. Priest Jaya. Keywords: Household appliance, Application Design, Android